2018
DOI: 10.7196/samj.2018.v108i7.12969
|View full text |Cite
|
Sign up to set email alerts
|

Describing key performance indicators for waiting times in emergency centres in the Western Cape Province, South Africa, between 2013 and 2014

Abstract: The triage process appears to improve waiting times for the sickest patients, although it is protracted throughout. Acutely ill patient journeys starting at CHC ECs suggested significant delays in care. Models need to be explored that allow appropriate care at the first point of contact and rapid transfer if needed. To improve waiting times, resource allocation in the emergency care system will need to be reconsidered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…In a Cape Town referral hospital, the median waiting time was 4.1 hours and 2.4 hours before and after introduction of the Cape triage score respectively [18]. A review of data from 52 Western Cape facilities revealed an overall mean waiting time of 2.1 hours [5]. The relatively poor performance of Princess Marina Hospital ED may be due to an overwhelmed system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Cape Town referral hospital, the median waiting time was 4.1 hours and 2.4 hours before and after introduction of the Cape triage score respectively [18]. A review of data from 52 Western Cape facilities revealed an overall mean waiting time of 2.1 hours [5]. The relatively poor performance of Princess Marina Hospital ED may be due to an overwhelmed system.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of quality emergency services is hampered by delays in the emergency department (ED). In fact emergency length of stay (LOS) is a key indicator of quality of care of health facilities and health departments [5]. It can therefore be used for performance monitoring and improvement of service.…”
Section: Introductionmentioning
confidence: 99%
“…It is recommended that patients triaged 'yellow' be seen within 1 h and patient's triaged 'green' be seen within 4 h. Despite these recommendations it is our anecdotal experience that because of patient overcrowding, which is a frequent problem in our ECs, patients may wait in excess of these time frames to be seen. 30,31 Thus, there has been much discussion in the literature of the advantages of nurse-driven analgesia at triage. 7,8 Our study has demonstrated that of a total of 976 individual medications prescribed for patients with minor trauma, only 145 (14.9%) were prescribed at presentation (at triage).…”
Section: Discussionmentioning
confidence: 99%
“…Performance indicators may consist of direct or indirect indicators (Holloway 2009;Parmenter 2012). Performance indicators can also be used to measure quality (Cohen and Bruijns 2018). Well-constructed performance areas contribute to improved performance by assisting individuals to gain a deeper understanding of their priorities and the outcomes they must achieve and to understand more clearly the connections between their roles and their relationship to the organisation's strategic objectives.…”
Section: The Role Of Indicators In Performance Managementmentioning
confidence: 99%